Literature as a resource in teaching the history of economic thought: economic analysis of The Merchant of Venice - Barbosa Castañeda Carlos Javier; Chaparro Germán Raúl (Sociedad y Economía, 2018)
This paper aims to present an economic analysis of The Merchant of Venice, as an illustration of how literature (and cinema) can be used as a resource and pretext to learn economics. This analytical exercise aims to illustrate the historical context of the mercantilist period, as well as to introduce some topics for reflection that schools of economic thought would later examine; for example, charging of interest, the importance of liquidity or the diversification of the investments’ portfolio. A synopsis of the play is presented, and the scenario is analyzed; it is complemented with comments or economic interpretations of some representative passages of this play. The results show, among others, the importance of considering institutional aspects in the study of economic relations and the need to correctly specify contracts.